Implementasi Hukum Pidana Sebagai Primum remedium terhadap Tindak Pidana Perdangan Satwa yang dilindungi : (Studi Putusan Nomor: 831/Pid.B-LH/2023/PN Tjk) - Joice Yokhebet Demina Sitepu; Eko Raharjo; Fristia Berdian Tamza (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The biodiversity found in Indonesia, both plants and animals, plays an important role in the ecosystem so it needs to be preserved. One example of animals is birds, which have a fairly high economic value, but hunting and bird trade can reduce their populations, resulting in extinction and ecosystem imbalances in nature. Many parties arbitrarily exploit or trade protected animals illegally. This journal analyzes how the application of criminal law as a primum remedium in the crime of trafficking in protected animals. The purpose of this journal is to find out the application of criminal law as a primum remedium in the crime of animal trafficking which is protected in the decision Number: 831/Pid.B-LH/2023/PN Tjk. The type of research used in writing this journal is a combination of normative juridical and empirical juridical evidence. The results of the research in the writing of this journal when associated with the case in the decision Number: 831/Pid.B-LH/2023/PN Tjk shows that the application of criminal law as a primum remedium to the crime of trafficking in protected animals occurs at the application stage which includes the investigation and investigation process by the police, prosecution by the prosecutor's office, and trial in court to the verdict that provides a prison sentence of 6 (six) months each and A fine of Rp 5,000,000.00 (five million rupiah) each was read out by the panel of judges, namely when the convicts were under the supervision of the correctional institution.